The Rainbow Connection Number of Triangular Snake Graphs - Rocha, Aleffer; Almeida, Sheila M.; Zatesko, Leandro M. (Anais do Encontro de Teoria da Computação (ETC); 2020: Anais do V Encontro de Teoria da Computação, 2020)
Rainbow coloring problems, of noteworthy applications in Information Security, have been receiving much attention last years in Combinatorics. The rainbow connection number of a graph G is the least number of colors for a (not necessarily proper) edge coloring of G such that between any pair of vertices there is a path whose edge colors are all distinct. In this paper we determine the rainbow connection number of the triple triangular snake graphs.